A combined cell and growth factor delivery for the repair of a critical size tibia defect using biodegradable hydrogel implants. (4th February 2022) - Cohen, Talia; Kossover, Olga; Peled, Eli; Bick, Tova; Hasanov, Lena; Chun, Tan Tuan; Cool, Simon; Lewinson, Dina; Seliktar, Dror
Abstract: The ability to repair critical‐sized long‐bone injuries using growth factor and cell delivery was investigated using hydrogel biomaterials. Physiological doses of the recombinant human bone morphogenic protein‐2 (rhBMP2) were delivered in a sustained manner from a biodegradable hydrogel containing peripheral human blood‐derived endothelial progenitor cells (hEPCs). The biodegradable implants made from polyethylene glycol (PEG) and denatured fibrinogen (PEG‐fibrinogen, PF) were loaded with 7.7 μg/ml of rhBMP2 and 2.5 × 10 6 cells/ml hEPCs. The safety and efficacy of the implant were tested in a rodent model of a critical‐size long‐bone defect. The hydrogel implants were formed ex‐situ and placed into defects in the tibia of athymic nude rats and analyzed for bone repair after 13 weeks following surgery. The hydrogels containing a combination of 7.7 μg/ml of rhBMP2 and 2.5 × 10 6 cells/ml hEPCs were compared to control hydrogels containing 7.7 μg/ml of rhBMP2 only, 2.5 × 10 6 cells/ml hEPCs only, or bare hydrogels. Assessments of bone repair include histological analysis, bone formation at the site of implantation using quantitative microCT, and assessment of implant degradation. New bone formation was detected in all treated animals, with the highest amounts found in the treatments that included animals that combined the PF implant with rhBMP2. Moreover, statistically significant increases in the tissue mineral density (TMD), trabecular number and trabecular thickness were observed in defects treated with rhBMP2 compared to non‐rhBMP2 defects. New bone formation was significantly higher in the hEPC‐treated defects compared to bare hydrogel defects, but there were no significant differences in new bone formation, trabecular number, trabecular thickness or TMD at 13 weeks when comparing the rhBMP2 + hEPCs‐treated defects to rhBMP2‐treated defects. The study concludes that the bone regeneration using hydrogel implants containing hEPCs are overshadowed by enhanced osteogenesis associated with sustained delivery of rhBMP2.